The Influence of Social Media Marketing, Product Quality, and Influences on Brand X Purchasing Decisions - Fenny, Fenny; Suryati, Lili (Dinasti Publisher, 2024)
The objective of this study is to determine the impact of social media marketing and product quality on the purchasing choices of Brand X items, while also examining the function of influencers as mediators, specifically among the generation-Z demographic. This study aimed to examine the interplay between Social Media Marketing, Product Quality Perceptions, Influencer Influence, and Purchasing Decisions in relation to Brand X items. This study employs a descriptive quantitative methodology, utilizing Google Form surveys as the data collecting tool. The target population for this research consists of individuals belonging to generation-Z who satisfy the specified research criteria. The data was examined using the regression method to quantify the impact of the independent variables (Social Media Marketing and Product Quality) on the dependent variable (Purchasing Decisions). The effectiveness of influencer mediation was assessed using path analysis and the Sobel test. The findings of this study indicate that Social Media Marketing and Product Quality exert an impact on Influencers. Product quality and influencers do not exert any impact on purchase decisions, however social media marketing does have an impact on purchasing decisions. Neither Social Media Marketing nor Product Quality exert any influence on Purchasing Decisions through Influencers as mediating variables.